CYBERING’S FUTURE ACCEPTANCE IN GERMANY AND INDONESIA - Ratna Kusuma Hening (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2015)
Cybering (cybersex) activities seem to be widely spread along with the countinuous development of the Internet and other online related-tools. This phenomenon confronts the existing traditional practice of sexuality and established culture and social norms, especially in eastern countries. This comparative study shows that there are no significant differences between Indonesian and German people in perceiving the ideas of sexuality and cybering. However, there is a quite difference in their acceptance on the cybering phenomenon if it will continuously exist in the future. It is revealed that Indonesians are more willing to accept the existence of cybering/cybersex activities in the future rather than Germans. Cultural and social aspects seem to be overshadowed with the more globalized society, which is also in line with the increasing penetration of the Internet and new media technology. Keywords: Cybersex; cybering; sexuality; culture; globalization